Application of a damage constitutive model to pile–slope stability analysis - Jiang, Jian-Hong; Huang, Xi-Long; Shu, Xiao-Rui; Ning, Xiao; Qu, Yan; Xiong, Wei-Lin (Frontiers in Materials, 2022)
Piles were regarded as elastic materials in the traditional numerical simulation. The elastic pile would not reflect the damage of the pile in engineering, which would misjudge the reinforcement effect of piles on slopes. The specific objective of this study was to propose a damage constitutive model to replace the traditional elastic constitutive model in the numerical analysis of pile-slope stability. The pile was simulated by a damage constitutive model in this study, which can reflect the plastic deformation of the pile. The factors of pile position and reinforcement ratio on a slope's safety of factor (FOS) are investigated by the finite difference method using FLAC3D. The lateral displacement, bending moment, shear force, and soil pressure of balance reinforced pile are used to study the difference between damage and elastic constitutive models. The results showed that the FOS considering the damage constitutive mode could be smaller around 15% than that considering an elastic constitutive model under specific conditions. Furthermore, the difference between the two evaluation results of the internal force of the same pile can reach about 30%. It was observed that the elastic constitutive mode would overestimate the reinforcement effect of the pile on the slope, which will cause potential safety hazards in engineering. This study provides a realistic damage constitutive model for the design and evaluation of slope-stabilizing piles.